2015
DOI: 10.1590/so100-720320150005321
|View full text |Cite
|
Sign up to set email alerts
|

Evolução temporal da prevalência de anemia em adolescentes grávidas de uma maternidade pública do Rio de Janeiro

Abstract: The results showed that the prevalence of anemia among pregnant adolescents seen at a public maternity is high. There was no reduction of anemia during the study period and other factors in addition to iron deficiency were involved in the genesis of anemia in this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0
11

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 14 publications
2
4
0
11
Order By: Relevance
“…Regarding the characteristics of prenatal care (PNC), some studies that evaluated the trimester of first consultation [ 34 ] and iron supplementation [ 6 , 7 , 19 , 21 ] corroborate the results of our research where the anemic parturients had their first consultation in the first trimester and took antianemic supplement.…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…Regarding the characteristics of prenatal care (PNC), some studies that evaluated the trimester of first consultation [ 34 ] and iron supplementation [ 6 , 7 , 19 , 21 ] corroborate the results of our research where the anemic parturients had their first consultation in the first trimester and took antianemic supplement.…”
Section: Discussionsupporting
confidence: 87%
“…The prevalence of anemia in Brazil ranges from 5% to high percentages considered severe (> 40%). [ 6 , 16 26 ] The data from current study corroborate the prevalence of anemia found in other municipalities in the North [ 18 ] and Northeast [ 19 , 21 ] regions, whose human development index (HDI) [ 27 ] are similar and above the percentage found in the South, [ 20 , 22 , 25 ] demonstrating that anemia is distributed in different ways, considering the geographic and socioeconomic diversity of each territory.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations